Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.3181/0703-rm-77
|View full text |Cite
|
Sign up to set email alerts
|

Heme Regulates Exocrine Peptidase Precursor Genes in Zebrafish

Abstract: We previously determined that yquem harbors a mutation in the gene encoding uroporphyrinogen decarboxylase (UROD), the fifth enzyme in heme biosynthesis, and established zebrafish yquem (yqe tp61 ) as a vertebrate model for human hepatoerythropoietic porphyria (HEP). Here we report that six exocrine peptidase precursor genes, carboxypeptidase A, trypsin precursor, trypsin like, chymotrypsinogen B1, chymotrypsinogen 1-like, and elastase 2 like, are downregulated in yquem/urod (2/ 2), identified initially by mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…This FSGD hypothesis was also suggested by Ohno (1970), then strongly supported by the findings of the 7 hox clusters distributed in different chromosomes in zebrafish and medaka (Amores et al, 1998;Naruse et al, 2000), and recently seemed to be confirmed by the analyses of fugu (Christoffels et al, 2004;Vandepoele et al, 2004) and tetraodon genomes (Jaillon et al, 2004). The FSGD hypothesis has been the most parsimonious explanation of the evolution of fish genes and gene families (Taylor et al, 2003;Wang et al, 2007aWang et al, ,b, 2008. For instance, my previous analysis of teleost fish period evolution is consistent with the FSGD hypothesis .…”
Section: Fish Clock Duplicates Were Generated From the Fish-specific mentioning
confidence: 68%
“…This FSGD hypothesis was also suggested by Ohno (1970), then strongly supported by the findings of the 7 hox clusters distributed in different chromosomes in zebrafish and medaka (Amores et al, 1998;Naruse et al, 2000), and recently seemed to be confirmed by the analyses of fugu (Christoffels et al, 2004;Vandepoele et al, 2004) and tetraodon genomes (Jaillon et al, 2004). The FSGD hypothesis has been the most parsimonious explanation of the evolution of fish genes and gene families (Taylor et al, 2003;Wang et al, 2007aWang et al, ,b, 2008. For instance, my previous analysis of teleost fish period evolution is consistent with the FSGD hypothesis .…”
Section: Fish Clock Duplicates Were Generated From the Fish-specific mentioning
confidence: 68%
“…This FSGD hypothesis also was initially suggested by Ohno (Ohno 1970), and recent mounting evidence such as the discoveries of the 7 hox clusters located in seven separate chromosomes in zebrafish and medaka (Amores et al 1998;Naruse et al 2000) and the whole genome analyses of fugu (Christoffels et al 2004;Vandepoele et al 2004) and tetraodon (Jaillon et al 2004) appears to confirm it. The FSGD hypothesis has been successfully used to account for the evolution of fish genes and gene families (Taylor et al 2003;Wang et al 2007;Wang et al 2008;Wang 2008a;b). The previous analyses of teleost fish period and clock evolution were consistent with the FSGD hypothesis (Wang 2008a;b).…”
Section: Discussionmentioning
confidence: 82%
“…We have previously established a heme-deficient zebrafish that is homozygous for a mutation in uroporphyrinogen decarboxylase ( urod ; also known as yquem ) as a model for studying human hepatoerythropoietic porphyria (HEP) (Online Mendelian Inheritance in Man number 176100) and heme deficiency pathogenesis (Wang et al, 1998). Our microarray and in situ hybridization analyses of this zebrafish HEP model revealed downregulation of six peptidase precursor genes – including carboxypeptidase A 5 ( cpa5 ), chymotrypsinogen 1 like ( ctr1l ), chymotrypsinogen B1 ( ctrb1 ), elastase 2 like ( ela2l ), trypsin precursor ( try ) and trypsin like ( tryl ) – specifically in the exocrine pancreas of the HEP zebrafish ( yquem/urod , −/− ) (Wang et al, 2007). Of these six zymogens, cpa5 (previously called cpa ) belongs to the MEROPS peptidase family M14, whereas the other five peptidases contain a trypsin-like serine protease (tryp_SPc) domain and are members of the serine peptidase chymotrypsin family S1 (chymotrypsin A, clan PA) (http://merops.sanger.ac.uk/) (Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Our microarray and in situ hybridization analyses of this zebrafish HEP model revealed downregulation of six peptidase precursor genes – including carboxypeptidase A 5 ( cpa5 ), chymotrypsinogen 1 like ( ctr1l ), chymotrypsinogen B1 ( ctrb1 ), elastase 2 like ( ela2l ), trypsin precursor ( try ) and trypsin like ( tryl ) – specifically in the exocrine pancreas of the HEP zebrafish ( yquem/urod , −/− ) (Wang et al, 2007). Of these six zymogens, cpa5 (previously called cpa ) belongs to the MEROPS peptidase family M14, whereas the other five peptidases contain a trypsin-like serine protease (tryp_SPc) domain and are members of the serine peptidase chymotrypsin family S1 (chymotrypsin A, clan PA) (http://merops.sanger.ac.uk/) (Wang et al, 2007). These serine peptidases function extracellularly to aid food digestion (Hedstrom, 2002; Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation